2022
DOI: 10.2337/dc21-1113
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention of Cardiovascular and Heart Failure Events With SGLT2 Inhibitors, GLP-1 Receptor Agonists, and Their Combination in Type 2 Diabetes

Abstract: OBJECTIVES To assess associations between current use of sodium–glucose cotransporter 2 inhibitors (SGLT2is), glucagon-like peptide 1 receptor agonists (GLP-1RAs), and their combination and risk for major adverse cardiac and cerebrovascular events (MACCE) and heart failure (HF) in people with type 2 diabetes. RESEARCH DESIGN AND METHODS In three nested case-control studies involving patients with type 2 diabetes in England an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 56 publications
1
62
0
2
Order By: Relevance
“…Last, Dr. Kawada proposed a discussion regarding the cardiovascular benefits of the combination of SGLT2 inhibitor and GLP-1 receptor agonist. We agree that these two drug classes, both individually and combined, are effective in reducing the risk of cardiovascular disease and death by different mechanisms [2][3][4]. However, this aspect is out of the scope of this study, as the primary outcome of our study was the efficacy of the combination therapy in terms of glycemic control for at Response https://doi.org/10.4093/dmj.2022.0166 pISSN 2233-6079 • eISSN 2233-6087 Diabetes Metab J 2022;46:665-666 Diabetes Metab J 2022;46:665-666 https://e-dmj.org least 1 year.…”
mentioning
confidence: 70%
“…Last, Dr. Kawada proposed a discussion regarding the cardiovascular benefits of the combination of SGLT2 inhibitor and GLP-1 receptor agonist. We agree that these two drug classes, both individually and combined, are effective in reducing the risk of cardiovascular disease and death by different mechanisms [2][3][4]. However, this aspect is out of the scope of this study, as the primary outcome of our study was the efficacy of the combination therapy in terms of glycemic control for at Response https://doi.org/10.4093/dmj.2022.0166 pISSN 2233-6079 • eISSN 2233-6087 Diabetes Metab J 2022;46:665-666 Diabetes Metab J 2022;46:665-666 https://e-dmj.org least 1 year.…”
mentioning
confidence: 70%
“…Another study of the dataset found 18.1 and 13.9 major adverse cardiovascular events (MACE) and HF events per 1000 person‐years of follow‐up among persons with T2D not having prior cardiovascular disease or prior HF, respectively; 2‐3% of persons in the data set used SGLT2i and glucagon‐like peptide 1 receptor agonists (GLP‐1RA), and 0.2‐0.3% used both. Use of SGLT2i, GLP‐1RA, and their combination was associated with 18%, 7%, and 30% lower odds of MACE, and with 51%, 18%, and 43% lower odds of HF events, respectively 11 …”
Section: Macrovascular Disease Treatment Approachesmentioning
confidence: 96%
“…Use of SGLT2i, GLP-1RA, and their combination was associated with 18%, 7%, and 30% lower odds of MACE, and with 51%, 18%, and 43% lower odds of HF events, respectively. 11 In a propensity score matched analysis of GLP-1RA use in the Taiwan National Health Insurance Research Database of >4 million persons with T2D from 1998 to 2018, the average compliance rate was 40% overall, but 65% for those with >251 days of GLP-1RA use; the hazard rate for stroke was 1.03, 0.83, 0.69, and 0.25 for those with 1-59, 60-153, 154-251, and >251 days of GLP-1RA use, respectively, 12 confirming randomized controlled trial evidence of benefit of these agents. Another analysis from Taiwan compared persons with T2D initiating glyburide or glipizide, which block cardiac mitochondrial ATP-sensitive potassium channels, with those initiating gliclazide or glimepiride, not having this effect, from 2007 to 2016; the former agents were associated with 1.2-fold greater risk of MACE than the latter, with 1.2-fold greater risk of stroke and 2.6-fold greater risk of cardiovascular death, with significant 4.7-fold increase in MACE risk appearing during the first 90 days of use of the agents.…”
Section: Hypoglycemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, the options for the very early prevention of HF were very limited, without significant improvement in cardiovascular outcomes. However, the enthusiasm for the primary prevention of HF visibly increased in recent years following the encouraging and clinically significant results established by SGLT2 inhibitor trials in patients with diabetes without HF 9. Nevertheless, further research is necessary to identify additional effective pathways to prevent HF in all comers, and non-invasive characterisation of myocardial microstructure could help target patients at increased risk of incident HF.…”
mentioning
confidence: 99%